2012
DOI: 10.1104/pp.111.190686
|View full text |Cite
|
Sign up to set email alerts
|

Type III Secretion and Effectors Shape the Survival and Growth Pattern of Pseudomonas syringae on Leaf Surfaces    

Abstract: The bacterium Pseudomonas syringae pv syringae B728a (PsyB728a) uses a type III secretion system (T3SS) to inject effector proteins into plant cells, a process that modulates the susceptibility of different plants to infection. Analysis of GREEN FLUORESCENT PROTEIN-expressing PsyB728a after spray inoculation without additives under moderate relative humidity conditions permitted (1) a detailed analysis of this strain’s survival and growth pattern on host (Nicotiana benthamiana) and nonhost (tomato [Solanum lyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 63 publications
(83 reference statements)
4
65
0
Order By: Relevance
“…These data indicate that pavement cells are sites for effector delivery by P. syringae. These findings are supported by previously published work, which demonstrated that transcription of avrPto in P. syringae was highest on the leaf surface when bacteria were in contact with pavement cells (Lee et al, 2012).…”
Section: Effectors Are Delivered Into Multiple Cell Types In Arabidopsupporting
confidence: 90%
See 1 more Smart Citation
“…These data indicate that pavement cells are sites for effector delivery by P. syringae. These findings are supported by previously published work, which demonstrated that transcription of avrPto in P. syringae was highest on the leaf surface when bacteria were in contact with pavement cells (Lee et al, 2012).…”
Section: Effectors Are Delivered Into Multiple Cell Types In Arabidopsupporting
confidence: 90%
“…Previous studies using P. syringae pv syringae B728a detected bacterial effector expression at 24 and 48 hpi on the leaf surface, and bacterial strains with mutations in the TTSS exhibited reduced epiphytic growth (Lee et al, 2012). In a natural infection, P. syringae initially colonizes the leaf surface, with aggregates forming at cell-cell junctions between pavement cells (Monier and Lindow, 2003b; Lee et al, 2012). We observed effector delivery at the pavement cell junctions ( Figure 4B), supporting cell junctions as important environmental niches for P. syringae colonization and initiation points for effector dissemination.…”
Section: Discussionmentioning
confidence: 97%
“…Syringolin A, a nonribosomal peptide and polyketide synthase present in some P. syringae pv syringae strains, is able to counteract stomatal immunity (Schellenberg et al, 2010). Furthermore, some P. syringe effectors enhance growth on the surface of plant leaves (Lee et al, 2012). The P. syringae effector HopM1 can suppress stomatal immunity (Lozano-Durán et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Extending these studies to other detection events has been facilitated by the advent of modern genomics approaches where genomics surveys have identified suites of bacterial virulence effectors independent of a specific virulence function (Lee et al, 2012). These effector surveys have shown that pathogens send a large suite of signals into the plant that if each was sensed and responded to by an independent suite of polymorphic genes could lead to a highly polygenic response system.…”
Section: Quantitative Basis Of Pathogen Perceptionmentioning
confidence: 99%